Bounded holomorphic projections for exponentially decreasing weights - Wolfgang Lusky; Jari Taskinen (Journal of Function Spaces and Applications)
We construct generalized Bergman projections on a large class of weighted L∞–spaces. The examples include exponentially decreasing weights on the unit disc and complex plane.